A comparison of training modality and total genotype scores to enhance sport-specific biomotor abilities in under 19 male soccer players - Suraci, B. R.; Quigley, C.; Thelwell, R. C.; Milligan, G. S. (The Journal of Strength and Conditioning Research, 2021)
Soccer-specific training (SST) and small-sided games (SSGs) have been shown to develop physical proficiency in soccer. Research on genetics and epigenetics in the prescription of training is limited. The aims of this study were to compare the impact of 3 different SST/SSG methods and investigate if a total genotype score (TGS) influences training response. Subjects (n = 30 male soccer players, mean ± SD; age 17.2 ± 0.9 years, stature = 172.6 ± 6.2 cm; body mass = 71.7 ± 10.1 kg) were stratified into a "power" (PG) or "endurance" (EG) gene profile group, where a 15 single nucleotide polymorphism panel was used to produce an algorithmically weighted TGS. Training 1 (T1—SSGs only), training 2 (T2—SSGs/SST), and training 3 (T3—SST only) were completed (in that respective order), lasting 8 weeks each, interspersed by 4-week washouts. Acceleration (10-m sprint) was improved by T2 only (1.84 ± 0.09 seconds vs. 1.73 ± 0.05 seconds; Effect Size [ES] = 1.59, p < 0.001). Speed (30-m sprint) was improved by T2 (4.46 ± 0.22 seconds vs. 4.30 ± 0.19 seconds; ES = 0.81, p < 0.001) and T3 (4.48 ± 0.22 seconds vs. 4.35 ± 0.21 seconds; ES = 0.58, p < 0.001). Agility (T-test) was improved by T1 (10.14 ± 0.40 seconds vs. 9.84 ± 0.42 seconds; ES = 0.73, p < 0.05) and T3 (9.93 ± 0.38 seconds vs. 9.66 ± 0.45 seconds; ES = 0.66, p < 0.001). Endurance (Yo-Yo level 1) was improved by T1 (1,682.22 ± 497.23 m vs. 2,028.89 ± 604.74 m; ES = 0.63, p < 0.05), T2 (1,904.35 ± 526.77 m vs. 2,299.13 ± 606.97 m; ES = 0.69, p < 0.001), and T3 (1,851.76 ± 490.46 m vs. 2,024.35 ± 588.13 m; ES = 0.35, p < 0.05). Power (countermovement jump) was improved by T3 only (36.01 ± 5.73 cm vs. 37.14 ± 5.62 cm; ES = 0.20, p < 0.05). There were no differences in T1, T2, and T3 combined when comparing PG and EG. The PG reported significantly (Chi2(20) = 4.42, p = 0.035, ES = 0.48) better training responses to T3 for power than the EG. These results demonstrate the efficacy of SSGs and SSTs in developing biomotor abilities. Although these results refute talent identification through the use of a TGS, there may be use in aligning the training method to TGS to develop power-based qualities in soccer.